Computing Reverberation Time in a 3D Room Model Using a Finite Difference Method Applied for the Diffusion Equation - Jarosław KRASZEWSKI (Archives of Acoustics)
The article presents theoretical values of reverberation times calculated on the basis of the diffusion equation for three room models: flat, cubic, and long. The article shows that not only the average absorp- tion coefficient, but also location of the absorbent material, as well as the place where the time is counted have an impact on the reverberation time, calculated on the basis of the diffusion equation. Despite that, the diffusion model is based on statistical assumptions. The primary goal of the article was to show that the model has geometrical features.